Building a consolidated community global cropland map - See, Linda; Fritz, Steffen; Thornton, Philip K.; Justice, Chris; Becker-Reshef, Inbal; Leo O; Herrero, Mario; You, Liangzhi (2012)
This paper describes the start of a data sharing process to develop a consolidated community cropland map, which was initiated through a recent workshop on characterizing and validating global agricultural land cover. Participants from different organizations around the world were asked to contribute their various cropland maps prior to the workshop. Other data such as geo-tagged photos, in-situ data, classified satellite images and videos also were provided as part of this process. The data are now available online at agriculture.geo-wiki.org. This data sharing exercise, which has culminated in a new Sub-task on Agricultural Mapping as part of the GEO Agricultural Monitoring Task, will continue as an ongoing process and represents an effective model for how data sharing could be facilitated across the GEO community.